Multitudes (Hors-serie) - Transmission (Hiver 2007). - Bakhtine, Mikhaïl; Bonopéra, Matthias; Boulanger, Sylvie; Fiat, Christophe; Fol, Jac; Hillaire, Norbert; Holmes, Brian; Kihm, Christophe; Lazzarato, Maurizio; Mangion, Eric; Moulier Boutang, Yann; Mouton, Joseph; et al. (Amsterdam : CNEAI (Centre National de l'estampe et de l'art imprimé) Chatou Multitudes Amsterdam Villa Arson Nice, 2007)
Serralongue, Bruno ; Magnin, Stéphane ; Filliou, Robert ; Pfeuffer, Joachim ; Osborne, Peter ; Fiat, Christophe ; Fol, Jac ; Hillaire, Norbert ; Sérandour, Yann ; Bonopéra, Matthias ; Bakhtine, Mikhaïl ; Mouton, Joseph ; Holmes, Brian ; Lazzarato, Maurizio ; Kihm, Christophe ; Boulanger, Sylvie ; Moulier Boutang, Yann ; Boyer, Edouard ; Mangion, Eric
Frans
boek